COMPLIANCE TO SURVIVING SEPSIS CAMPAIGN HOUR–1 BUNDLE–A CROSS SECTIONAL STUDY AMONG PHYSICIANS INVOLVED IN CRITICAL CARE IN PAKISTAN - Feroze, Rehana; Tariq, Muhammad; Toor, Abdul Wasay (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine physician’s compliance to surviving sepsis campaign updated Hour-one bundle incritically ill patients in Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: Department of Anaesthesiology, Combined Military Hospital Lahore MedicalCollege, from Jun to Aug 2019.Methodology: This study was carried out among physicians managing critical patients in intensive care units.Participants were asked to fill out a 16-questions survey (work experience, qualification and individual components of surviving sepsis campaign hour-1 bundle. Data was collected using online access to survey and by sending hard copies.Results: Questionnaire was sent to 230 physicians while only 63 responses were received (response rate 27%).Only 45 (71%) respondents were aware of the updated Hour-1 bundle. There was no institutional protocolfor compliance to sepsis bundles in thirty three (55%) responses. 52% respondents used Systemic inflammatoryresponse syndrome (SIRS) criteria to diagnose sepsis while quick Sequential Organ Failure Assessment (qSOFA)was used by 36% respondents. Overall compliance to hour-1 bundle components was only 60%. Lactate levelswas not measured by 35 (55%) respondents while 24 (38%) did not obtain blood cultures before administeringantibiotics. Crystalloid and nor epinephrine was used by all respondents. Overall compliance with all the components of sepsis bundle had strong correlation with post-graduate qualification (p-value 0.001-0.049).Conclusion: Poor compliance to updated sepsis guidelines was one of the major reasons of high sepsis relatedmortality in Pakistan.